Influence of Geometry and Boundary Conditions in Area of Cohesion between Materials on the Reflection of an Ultrasonic Beam. Part 1. Theoretical research - A. R. Bayev; A. L. Mayorov; N. V. Levkovich; D. V. Shavlovskiy; M. V. Asadchaya (Приборы и методы измерений)
The improvement of efficiency, reliability and productivity of ultrasonic testing of objects with cohesion between materials connected by welding, soldering, gluing, etc. is 'an important problem of the modern production technologies. The purpose of the paper is to determine in 3D space the conditions for increasing the sensitivity and reliability of the flaw detection in the cohesion zone between materials when the form of defect interface can be different.In the first part of the theoretical study the features of the formation of the acoustic fields of ultrasonic waves scattered from solid's interface when spot of an acoustic beam crosses the boundary of the defective region in the shape of an ellipse or a long strip have been investigated. In this case, the boundary conditions in the defect area change discretely or linearly.It was suggested to use a phase shift between reflected waves from the defect and defect-free interfaces as the more informative parameter depending on the cohesion between materials. There is shown that there are conditions to achieve sufficiently high sensitivity detection of interface defects when the scattered waves receiving are to be at angles outside the main directivity lobe of the scattering field pattern. The evolution features of the scattering field structure which are needed for the development of the method of evaluation the cohesion of materials has been got.